2017
DOI: 10.1016/j.polymertesting.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Elastic recovery after compression in HNBR at low and moderate temperatures: Experiment and modelling

Abstract: Elastic recovery after compression or compression set is one of the key indicators of elastomer performance in sealing applications, such as O-rings in flange joints. In this work, findings of a study of the compression set property of a hydrogenated nitrile butadiene rubber (HNBR) at temperatures above and below the glass transition temperature T g are presented. The compression set in the elastomer is found to increase with cooling up to 100 % at the glass transition temperature and decrease with time after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 15 publications
(26 reference statements)
3
14
0
Order By: Relevance
“…For a sealing material, SR results in a decrease of contact pressure potentially leading to reduced sealing capability. SR also correlates well with the compression set in elastomer seals [3].…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…For a sealing material, SR results in a decrease of contact pressure potentially leading to reduced sealing capability. SR also correlates well with the compression set in elastomer seals [3].…”
Section: Introductionmentioning
confidence: 52%
“…The relaxation spectrum is a very useful characteristic of an elastomer that enables the prediction of other viscoelastic characteristics, e.g. the compression set [3]. The generalized Maxwell model is deployed to fit the CSR master curves using the sign control method (SCM) [47] and obtain the viscoelastic parameters for both compounds.…”
Section: The Effect Of Carbon Blackmentioning
confidence: 99%
See 1 more Smart Citation
“…Two formulations were used: one with 20.4 Vol.% N-330 HAF carbon black (CB) loading and the other without it (further referred to as unfilled HNBR). The full description of the material composition, the processing details and the material properties were provided in the previous publications [19,20,21]. It is important to mention that the elastomers have a T g of about −16 • C as determined by dynamic mechanical thermal analysis (DMTA) experiments at the measurement frequency f of 1 Hz [20] or −23 • C as determined from differential scanning calorimetry (DSC) measurements conducted using a heating rate of 20 • C/min [19].…”
Section: Methodsmentioning
confidence: 99%
“…Most of the earlier investigators used commercial seals with scarcely reported low-temperature properties of the seal materials (typically only the glass transition T g and sometimes 10 % retraction TR-10 temperatures) and the sealed surface properties. Therefore, the mechanisms of cold leakage of elastomeric seals have remained unclear, except for the case where the sealing gap was artificially increased and seals failed due to their slow elastic recovery at low temperatures near their T g [13,16,20]. This is, however, an extreme scenario which will not be considered herein.…”
Section: Introductionmentioning
confidence: 99%